Penerapan Konseling Singkat Berfokus Solusi untuk Meningkatkan Tanggung Jawab Siswa dalam Belajar - Fatin Az-Zahra; Siti Nurhaliza Muda; Nadia Afrillia A.R; Bagus Pribadi; Yenti Arsini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Solution-oriented brief counseling is a fast and effective counseling approach in solving student problems. This approach emphasizes students' skills and strengths, focuses on the solutions they want to achieve, avoids past problems, and focuses on the future to achieve the desired goals. Solution Focused Brief Therapy (SFBT) involves brief counseling sessions that focus on solutions rather than problems. This research aims to determine the effectiveness of implementing short solution focused counseling to increase student ownership of their learning. The method used is library research and data was obtained using library research. The research results show that the use of short, solution-oriented advice is effective in increasing student responsibility in their learning. Students who received short-term tutoring significantly increased their learning responsibilities compared to a control group that did not receive advising. Therefore, schools and teachers are encouraged to implement brief counseling as a strategy to increase student ownership of their learning.